PENGARUH REALISTIC MATHEMATIC EDUCATION (RME) TERHADAP PEMAHAMAN KONSEP PERKALIAN BILANGAN BULAT SISWA SEKOLAH DASAR - Lindiawati, Elin; Jenal Mutaqin, Ejen; Nadiroti Muslihah, Neni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of the Realistic Mathematics Education (RME) approach on fourth-grade students’ conceptual understanding of integer multiplication at SDN 1 Ngamplangsari. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 40 students, including 20 students in the experimental class and 20 students in the control class. Data were collected through a conceptual understanding test and analyzed using the Independent Sample t-Test and N-Gain analysis. The results showed that the experimental class mean score increased from 61.25 on the pretest to 81.00 on the posttest, while the control class increased from 59.25 to 62.00. The Independent Sample t-Test yielded a significance value of 0.000 < 0.05, indicating a significant effect of the RME approach on students’ conceptual understanding. Furthermore, the N-Gain score of 67.97% indicated that the implementation of RME was moderately effective. Therefore, the RME approach significantly improves elementary school students’ conceptual understanding of integer multiplication.